Juridical Study of Ownership Rights over Apartment Units on Land with Building Use Rights for Foreign Citizens - Anang Muhammad Rizaldi; Ida Bagus Agung Mahesora Mas; Christian Isacc Alexander Alianto; Nur Imam (NOTARIIL Jurnal Kenotariatan, 2025)
Indonesia has great potential in the field of tourism, especially in Bali, which encourages foreign nationals (WNA) to own residences in Indonesia. However, land ownership by foreign nationals is restricted by provisions in the Basic Agrarian Law (UUPA). This study aims to examine the ownership status of apartment units built on Land Use Rights (HGB) for foreign nationals, as well as to trace the normative conflicts arising between the UUPA and the provisions in Law Number 6 of 2023 and Government Regulation Number 18 of 2021. The research method used is normative legal research with a legislative and conceptual approach. The results show that although the latest provisions allow foreign nationals to own apartment units on HGB land, this contradicts Article 36 of the UUPA, which restricts HGB subjects only to Indonesian citizens and Indonesian legal entities. The conclusion from this study is that foreign ownership of apartment units on HGB land creates a conflict of norms, and such ownership should only be permitted on use-right land in accordance with the provisions of the UUPA.